Multi Objective Optimization on the Basic of Ratio Analysis untuk Pemilihan Pestisida - Sukamto Sukamto; Randi Andria Nugrah (Maranatha University Press, 2023)
The use of pesticides in agriculture plays a role in preventing and reducing diseases in chili plants. Pesticides for chili plants are quite widely spread on the market and have the advantages of each product offered to farmers, so farmers must be more careful and understanding in choosing pesticides to be used in preventing chili plant diseases. For that we need a decision support system (SPK). The data used in this research are 10 types of pesticides as an alternative. While the criteria are determined based on the agriculture and food service, namely price, classification, number of diseases eradicated, method of action, shelf life, and formulation concentration. Data analysis uses the MOORA method to support decision making for farmers in providing an assessment of the best pesticides on chili plants. The research results obtained for the three best pesticides are Tridex 80 WP, Lamzeb 85 WP, and Ziflo 76 WG.